The Influence of Compensation Allowances and Work Motivation on Employee Performance at PT KGS - Monica, Shania; Sudinta, Heru; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The Compensation of benefits and Motivation of works on Employee Performance in the PT KGS. This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all employees at PT KGS. The sample size was 90 respondents. The sampling technique used was simple random sampling. The Slovin formula was used to determine a representative sample size in quantitative research. Data collection techniques included observation, questionnaires, and documentation. Data analysis employed multiple linear regression analysis using SPSS 26. Data validity was verified through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, the Compensation of benefits significantly influences the performance of at PT KGS, which is indicated by the calculated t value > t table ((13,510>1,985) and a significance value of 0.000 is smaller than the significance value of 0.05. This Ha is accepted and H0 is rejected. (2) Partially, Motivation of works significantly influences the performance of employees in the Preparation section at PT KGS, which is indicated by the calculated t value > t table (9,696>1.985) and a significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, the work environment and compensation significantly influence the performance of employees in the PT KGS, which is indicated by F count > F table (127,604>3.09) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that work environment and compensation Compensation of benefits and Motivation of works variables, both partially and simultaneously, have a significant influence on the performance of employees in the PT KGS.